Efektivitas ekstrak daun pandanwangi sebagai insektisida nabati dalam mengurangi jumlah lalat selama penjemuran ikan patin asin - Hilyati Fadhlah; Feliatra Feliatra; Rahman Karnila (Pelantar Press, 2018)
The size of the fly population at the time of Salted Catfish production (SC) is one of theimportant problems that will have an impact on the health and deterioration of fish quality, as well ashaving an impact on socio-economic conditions. Flies are mechanical vectors for the transmission ofdiseases carried through microorganisms Staphylococcus aureus (S.aureus). To deal with this problemproducers use chemical insecticides which are sometimes used at inappropriate dosages, so that they willadversely affect human health and the environment. therefore it is used by Fragrant Pandan Leaves(FPL) which have chemicals as poisons for vectors and safe for humans. This study aims to identify thecontamination of S.aureus bacteria in SC from Penyasawan Village, to analyze the effectiveness of FPLextracts in reducing the number of flies in the process of drying the SC on product acceptance. Usingexperimental research methods, with RAL, it was carried out at the UPTD laboratory for fish diseasesand the water quality of the Kampar Regency Fisheries Service. Data were analyzed using the One-WayANOVA statistical test. The results showed that, for the most part Salted Catfish from PenyasawanVillage is identified contamination of Staphylococcus aureus bacteria. Pandan Wangi Leaf Extract caneffectively reduce the density of flies that perch during drying of Salted Catfish with the highestconcentration having the greatest resistance to the flies of flies. Salted Catfish soaked in Pandan Wangileaves are in demand by consumers